EVOLUSI MANUSIA DALAM AL-QURâ€™Ä€N Studi terhadap Taâ€™wil Muá¸¥ammad Syaá¸¥rÅ«r atas Surah az-Zumar/39: 6 - Aniroh, Reni Nur (Lajnah Pentashihan Mushaf Al-Qur'an, 2017)
This paper discusses MuÃ¡Â¸Â¥ammad SyaÃ¡Â¸Â¥rÃ…Â«rÃ¢â‚¬â„¢s interpretation of Surah az-Zumar/39: 6 on the origin of living things, paticularly on the origin of human creation. In connection with this study, most interpreters believe that human creation was started from nafs wÃ„ÂÃ¡Â¸Â¥idah (one soul) which was interpreted as Adam, and zaujahÃ„Â (his partner) as Ã¡Â¸Â¤awÃ„ÂÃ¢â‚¬â„¢. But, SyaÃ¡Â¸Â¥rÃ…Â«rÃ¢â‚¬â„¢s interpretation concludes that the human creation (as well as other living beings) begins from a single-celled organism, namely nafs wÃ„ÂÃ¡Â¸Â¥idah (one soul) that then develops through sexual process after a long phase of evolution. This concept is taken from the interpretation of Ã¡Â¹Â¡umÃ„Â jaÃ¢â‚¬â„¢ala minhÃ„Â zaujahÃ„Â (then We create from the soul its partner). This interpretation is interesting to observe critically, because besides unique, it can answer the accusation of the proponents of creationism tending to put theory of evolution in contrary with the faith in God. Keywords: MuÃ¡Â¸Â¥ammad SyaÃ¡Â¸Â¥rÃ…Â«r, human creation, QurÃ¢â‚¬â„¢an, evolution.